Identification Bacterial Contaminant in Semiarundinaria fastuosa Tissue Culture - Wulandari, Erna; Retnaningrum, Endah; Sembiring, Langkah (Proceeding International Conference on Science and Engineering, 2020)
Bamboo is one of the plants which propagated by tissue culture technique however, the emergence of microbial contaminant caused decrease of bamboo production. A type of microbe that caused the contamination on Semiarundinaria fastuosa tissue culture is bacteria. This study aimed to isolate bacterial contaminant and understanding its biodiversity. Bacterial isolation and phenotypic characterization were done by observing morphology, physiological test, biochemical test, identification and numeric phenetic analysis. Twelve bacterial contaminants was isolated and based on profile matching with Bergey’s Manual of Determinative Bacteriology, six isolate was a member of genus Bacillus, one isolate Enterococcus, two isolate Xenorhabdus, one isolate Morococcus, one isolate Corynebacterium, and one isolate belongs to genus Sarcina. A dendrogram created using Simple Matching coefficient (SSM) parameter and average linkage algorithm shown that on the 71% similarity index, all 12 OTU was grouped in one cluster. However, a dendrogram produced by Jaccard’s coefficient (SJ) parameter and average linkage algorithm on 70% similarity index divided 12 OTU on to 12 clusters.